AN ANALYSIS OF TRANSLATION STRATEGIES FOR NON-EQUIVALENCE USED IN LIAN GOUW'S NOVEL ONLY A GIRL AND ITS INDONESIAN VERSION ONLY A GIRL-MENANTANG PHEONIX - Dita Wijayanti N.K Mirahayuni (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2014)
This article reports a study of the translation strategies used in solving the problems of non-equivalence in translating English text into Indonesian. The study adopts Bakerâ€™s (1992) classification of translation strategies. The text being investigated are an English novel by Lian Gouw entitled Only A Girl (2009) and its Indonesian version entitled Only A Girl-Menantang Phoenix (2010). Using descriptive qualitative research design, the study attempts to identify and find explanation of the translation strategies used in 105 sentences, collected up to the fifth chapter of the novel. The result of the study shows that, from 105 data, seven strategies are found to be used in the translation: (a) translation by superordinate/more general word (12 data), (b) translation by a more neutral or less expressive word (3 data), (c) translation by cultural substitution (9 data), (d) translation using a loan word or loan word plus explanation (6 data), (e) translation by paraphrase using a related word (18 data), (f) translation by paraphrase using unrelated words (21 data), and (g) translation by omission (36 data). The choice of the strategies depends on the context of the text and shows the translatorâ€™s attempt to present a clear meaning of the text, particularly when the items are not lexicalized in the target language.Â